Epoxidized vegetable oils plasticized poly(lactic acid) biocomposites: mechanical, thermal and morphology properties - Chieng, Buong Woei; Ibrahim, Nor Azowa; Then, Yoon Yee; Loo, Yuet Ying (MDPI, 2014)
Plasticized poly(lactic acid) PLA with epoxidized vegetable oils (EVO) were prepared using a melt blending method to improve the ductility of PLA. The plasticization of the PLA with EVO lowers the Tg as well as cold-crystallization temperature. The tensile properties demonstrated that the addition of EVO to PLA led to an increase of elongation at break, but a decrease of tensile modulus. Plasticized PLA showed improvement in the elongation at break by 2058% and 4060% with the addition of 5 wt % epoxidized palm oil (EPO) and mixture of epoxidized palm oil and soybean oil (EPSO), respectively. An increase in the tensile strength was also observed in the plasticized PLA with 1 wt % EPO and EPSO. The use of EVO increases the mobility of the polymeric chains, thereby improving the flexibility and plastic deformation of PLA. The SEM micrograph of the plasticized PLA showed good compatible morphologies without voids resulting from good interfacial adhesion between PLA and EVO. Based on the results of this study, EVO may be used as an environmentally friendly plasticizer that can improve the overall properties of PLA.